To determine if \( x = -3 \) is a solution to the quadratic equation \( -3x^2 - 9x = 0 \), we need to substitute \( x = -3 \) into the equation and see if it holds true.
Starting with the equation: \[ -3x^2 - 9x = 0 \]
Substituting \( x = -3 \): \[ -3(-3)^2 - 9(-3) = 0 \]
Calculating \( (-3)^2 \): \[ -3(9) - 9(-3) = 0 \]
Now simplify: \[ -27 + 27 = 0 \]
This simplifies to: \[ 0 = 0 \]
Since both sides of the equation are equal, \( x = -3 \) is indeed a solution to the quadratic equation \( -3x^2 - 9x = 0 \).